Political Attitude of the 212 Alumni towards Muhaimin Iskandar as a Candidate for Vice Presidentiality of Anies Baswedan - Virginia Pacina Nan Tampukmas; Abdul Ghofur (Journal La Sociale, 2024)
The General Election is an event where the public can choose their leaders openly and compete between the three presidential candidates, namely Lt. Gen. TNI (Ret.) H. Prabowo Subianto Djojohadikusumo, H. Ganjar Pranowo, S.H., M.I.P., and H. Anies Rasyid Baswedan, S.E., M.P.P., Ph.D. The third candidate certainly has their strategy for selecting a vice presidential candidate and how to campaign. Anies Rasyid Baswedan and Muhaimin Iskandar, as candidate pair number 1, experienced many challenges in getting public support. This research aims to explore the political attitudes of the Persaudaraan Alumni 212 community organization using interpretative qualitative methods to understand social phenomena through Bryman's interpretation process. Meanwhile, to find out the extent of the truth of the research, the author uses qualitative data analysis techniques starting from data collection and data analysis, data reduction, data presentation, and conclusions. The results of the research show that, on average, the administrators and members of the Persaudaraan Alumni 212 showed cognitive, affective and conative components regarding Muhaimin Iskandar's candidacy as Anies' vice-presidential candidate, who then ultimately accepted candidate number 1 because of the mental that resulted from joint deliberations and produced Itjima Ulama.